Schwannoma of the Tongue in a Paediatric Patient: A Case Report and 20-Year Review - Nitin Bhola; Anendd Jadhav; Rajiv Borle; Gaurav Khemka; Umesh Bhutekar; Sanatan Kumar (Case Reports in Dentistry)
Schwannomas (Neurilemmomas) are benign, encapsulated, slow-growing, and usually solitary tumours originating from Schwann cells of the peripheral nerve sheath with uncertain etiology. Approximately 25–48% of cases are seen in the head and neck region, of which 1% appears in the oral cavity. Lingual schwannoma can affect all age groups with peak incidence between the third and sixth decade. We report a rare case of lingual schwannoma in a 14-year-old girl complaining of asymptomatic swelling over lateral border of tongue since two years. Clinical examination revealed a nodule 1.5×1 cm in size, rubbery, nontender, smooth at right lateral border of tongue covered by normal mucosa, with no cervical lymphadenopathy. Excisional biopsy of the lesion was done under local anaesthesia. The histological sections spindle cells with thin wavy nuclei arranged as typical Antoni A (with Verocay bodies) and Antoni B areas. Nuclear palisading distribution (typical of a schwannoma) was readily identifiable. The patient was recurrence-free after one year.